A EXPLORING ISLAMIC VALUES THROUGH THE TAPE LEARNING MODEL (Tanamkan, Amati, Praktikkan, Evaluasi) - Zulfah, Zulfah; Sam, Zulfiah; Husnussaadah, Husnussaadah; Rahmawati, Rahmawati; Makmur, Makmur (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: In the face of rapidly changing global dynamics and the increasing challenges related to moral and ethical values, education plays a critical role in fostering intellectual and moral integrity. Islamic Religious Education (PAI) has long been responsible for instilling Islamic values in the younger generation, yet traditional methods often fail to address the practical application of these values in daily life. Purpose: This study explores the TAPE (Instill, Observe, Practice, Evaluate) learning model in PAI education, which integrates theory and practice to promote both intellectual and moral development. The TAPE model consists of four interconnected stages designed to facilitate students' understanding of Islamic values while fostering active engagement, social skills, and self-reflection. Method: A qualitative approach with a descriptive case study design was adopted for this research, involving both field and library research. Data collection included interviews, observations, and document analysis. Result: The study examines how the TAPE model enhances students' ability to internalize Islamic values, such as honesty, responsibility, and compassion, while also developing essential life skills. Findings suggest that the TAPE model not only promotes intellectual learning but also shapes students' character and encourages the application of Islamic values in their daily lives. Conclusion: The research concludes that the TAPE model is crucial in developing a generation that is both knowledgeable and morally grounded, ready to contribute positively to society. The study underscores the importance of adopting innovative pedagogical approaches like TAPE to address the challenges posed by globalization and moral integrity in modern Islamic education.